Inserção e desenvolvimento profissional de professores iniciantes na Educação Superior: desafios e aprendizados no IFCE - Guimarães, Marília Duarte (2024)
This research investigates the insertion and professional development of beginning teachers in Higher Education at the Federal Institute of Education, Science and Technology of Ceará (IFCE). The research aims to understand aspects that characterize professional insertion at IFCE in order to identify challenges and learning experiences of beginning teachers and to understand how institutional policy contemplates their development as teachers. To carry out this study, I developed a theoretical-empirical research with a qualitative approach based on Dialectical Historical Materialism, having as its main methodological foundation the categories of totality and contradiction that guided the analysis of data produced by several procedures such as, expanded bibliographic review with systematic review of academic productions, autobiographical writing, field diary, electronic questionnaire applied to 26 beginning teachers and narrative interviews conducted with two beginning pedagogical teachers at IFCE. The data highlight the main challenges faced by beginning teachers at the institution and reveal strategies developed by them based on the experiences and professional knowledge mobilized at the beginning of their careers in dialogue with Marcelo (1999; 2009; 2010), Vaillant and Marcelo (2012), Tardif (2011), Ávalos (2008), Romanowski (2012) Cruz, Farias and Hobold (2020) and Cunha (2016). These authors base our understanding of the professional development of beginning teachers in the process of professional insertion, considering the experiences of teachers in their own professional development path to formulate strategies to support beginning teachers in Higher Education. The research indicates that beginning teachers have difficulties of a pedagogical, institutional and personal nature. In addition, it reveals that teachers at the beginning of their careers in Higher Education learn as they modify their beliefs, that they feed back into their practices with feedback from students, and that they learn from the collaboration of peers and from militant social practice. Based on these experiences, I present a critical contribution to the design of policies for the insertion of teachers in the federal education system. Among the competing meanings of the construction of a professional insertion policy, I advocate a situated insertion accompanied by a teacher induction program or action that approaches learning communities as a space for reflecting on their own beliefs and sharing daily practices, emotions and concepts with peers in the context of work. This induction policy must include a training space on the foundations of pedagogical work, codes and the functioning of institutional culture, articulated with the problematization of teaching work conditions and the valorization of the career; an action that does not increase the work overload to which teachers are already subjected nor deepen the platformization of teaching work, but is committed to deepening democracy and escaping social control; a teacher induction policy committed to continuous professional development and that has as its reference point the educational praxis based on a broad social project, which has as its virtue emancipated training and assumes teacher autonomy as the center of professional insertion itself. Finally, the data make explicit the thesis that the absence of a professional insertion policy worsens the precariousness of teaching work and harms professionals' decision to remain in the profession, professional development in the first years of teaching and the feeling of belonging that has repercussions on the quality of professionalism in the public service.